Green Synthesis of Copper Nanoparticles Using Gynura procumbens Leaf Extract as a Bioreductant and Their Antibacterial Activity Against Escherichia coli - Nancy Rivana; Suyatno Sutoyo; Radita Yuniar Arizandy; Wahyu Setyarini (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2026)
Copper nanoparticles (CuNPs) are nanomaterials extensively utilized in optics, electronics, biology, catalysis, and as antibacterial agents. Sustainable synthesis approaches employing plant-derived bioreductants have garnered significant attention. In this study, CuNPs were synthesized via green chemistry using Gynura procumbens leaf extract as a bioreductant. Synthesis was performed by combining the leaf extract with 0.1 M CuSO₄ solution at volume ratios of 1:1, 1:2, 1:3, and 1:4. The mixture with the optimal volume ratio was further optimized at pH values of 8, 9, 10, and 11. The resulting CuNPs were characterized by UV-Vis spectroscopy, FTIR, and PSA. Antibacterial activity against Escherichia coli (ATCC 25922) was evaluated using the disk diffusion method. Optimal synthesis was achieved at a 1:2 volume ratio and pH 8. The CuNPs exhibited a maximum UV-Vis absorption at 316 nm, an average particle size of 8.23 nm, and a polydispersity index of 0.1631. FTIR spectra confirmed Cu–O bond vibrations at 457.64 and 617.14 cm-1. The synthesized CuNPs demonstrated strong antibacterial activity against E. coli, with an inhibition zone diameter of 13.89 ± 0.45 mm. These findings suggest that CuNPs synthesized via green methods using G. procumbens extract as a bioreductant have potential as antibacterial agents, particularly against E. coli.